New Pyrimidine-based Photo-switchable Bent-core Liquid Crystals - M. M., Yusoff; Hegde, Gurumurthy; Lutfor, M. R.; Muhammad Nor Fazli, Abd Malek; Srinivasa, Hosapalya T.; Kumar, Sandeep (Royal Society of Chemistry, 2013)
The first examples of liquid crystalline pyrimidine-based photo-switchable bent-core monomers incorporating azobenzene as side arms linked with terminal double bonds as polymerizable functional groups are synthesized and characterized. Polarizing optical microscopy (POM), differential scanning calorimetry (DSC) and X-ray diffraction analysis reveal that the bent-shaped lower homologue compounds are crystalline in nature whereas higher homologue compounds display the stable enantiotropic B6 phase. They exhibit fast photoisomerization effects in solution and relatively slow photoisomerization effects in liquid crystal cells. In solution both trans–cis and cis–trans occur at around 3 s and 200 s, respectively, whereas in solids they occur at around 10 s to 200 min. These are some of the first examples of azobenzene liquid crystals which exhibit very fast switching properties in solutions.